2015
DOI: 10.1099/vir.0.000214
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of the gene-inactivating potential of retroviral restriction factors APOBEC3F and APOBEC3G

Abstract: APOBEC3 (A3) proteins are host-encoded restriction factors that inhibit retrovirus infection by mutagenic deamination of cytosines in minus-strand DNA replication intermediates. APOBEC3F (A3F) and APOBEC3G (A3G) are two of the most potent A3 enzymes in humans with each having a different target DNA specificity. A3G prefers to deaminate cytosines preceded by a cytosine (59-CC), whereas A3F preferentially targets cytosines preceded by a thymine (59-TC).Here we performed a detailed comparative analysis of retrovi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…A3G mutation of GG to AG is effective in inactivating virus prior to integration, and A3F's GA-to-AA mutations are fewer and relatively ineffective (61). Thus, it seems unlikely that GA-to-AA mutation plays a decisive role in the equivalent susceptibilities of JRCSFvif42/43DW79S and JRCSF⌬vif to extinction.…”
Section: Discussionmentioning
confidence: 99%
“…A3G mutation of GG to AG is effective in inactivating virus prior to integration, and A3F's GA-to-AA mutations are fewer and relatively ineffective (61). Thus, it seems unlikely that GA-to-AA mutation plays a decisive role in the equivalent susceptibilities of JRCSFvif42/43DW79S and JRCSF⌬vif to extinction.…”
Section: Discussionmentioning
confidence: 99%
“…Low levels of mutations or missense mutations may result in either HIV-1 evolution or have a neutral effect, rather than HIV-1 inactivation [16, 42, 67, 68, 69, 70, 71]. Studies have demonstrated that due to the A3G preferred deamination motif, A3G-induced mutagenesis is likely to induce viral inactivation [50, 64, 66, 72, 73, 74]. However, the A3s that cause 5′GA → 5′AA mutations (A3F, A3H, and A3C) may be more likely to induce HIV-1 genetic diversity and evolution [17, 64, 74].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have demonstrated that due to the A3G preferred deamination motif, A3G-induced mutagenesis is likely to induce viral inactivation [50, 64, 66, 72, 73, 74]. However, the A3s that cause 5′GA → 5′AA mutations (A3F, A3H, and A3C) may be more likely to induce HIV-1 genetic diversity and evolution [17, 64, 74]. These data in combination with data demonstrating that during chronic HIV-1 infection Vif can acquire mutations that partially decrease its ability to induce A3 degradation suggest that HIV-1 can manipulate A3 activity like a mutational rheostat [44, 45, 68].…”
Section: Introductionmentioning
confidence: 99%
“…Among the four APOBEC3 members containing double CD domains, A3F and A3G show potent anti-HIV activities 25; 26; 27; 28; 29; 30 , which is through incorporation/encapsidation of the APOBEC3 enzymes into HIV virions 31; 32; 33; 34 . The incorporation/encapsidation into HIV virions, which is mainly mediated through RNA binding by the A3 proteins, requires both CD1 and CD2 domains of A3F, whereas only CD1 of A3G is needed 32; 34; 35; 36; 37; 38; 39 .…”
mentioning
confidence: 99%